Variasi Tutur “Helmi” Penderita Afasia Suatu Kajian Morfo-Neurolinguistik - Johan, Mhd (Asosiasi Ide Bahasa Kepri, 2024)
This research aims to identify speech events uttered by a respondent named Helmi. The theory used to identify data is neurolinguistics theory initiated by Ingram and Sastra, while for morphological studies the author uses Johan and Susanto's theory. After this theory, the author uses methods, there are two methods, first the data collection method and the data analysis method. For the data collection method, the author uses the skillful listening and involvement method or the agih method. This method was initiated by Nadra and Renidawati. To analyze the data the author uses the method for direct elements. This technique is also supported by the loss technique, the addition technique and the replace technique, this method and technique is the Sudaryanto technique. Once these methods and techniques are involved, results are obtained. The results obtained in this analysis are three processes. These processes are the replace process, add process, and replace process. The results obtained are the morphemes /bukan/> /buka/, /komunikasi/>/komunikai/, /maukah/>/baukah/, /dada/> /tata/ and /rumah/ > /rumba/. In terms of appearance, the replacement process occurred 3 times and the process disappeared three times.